Small business’ motivation for organic production in the agricultural sector of the North-West - Natalya A. Nikonova; Aleksey G. Nikonov; Khapsat A. Dibirova (Крестьяноведение, 2025)
The article considers the possibility of sustainable development of the national organic market by affecting the motivation of local producers. The authors mention theoretical approaches to the study of the relationship between incentive factors and economic behavior and present the results of the survey of heads of farms in the Leningrad, Novgorod and Pskov Regions (N=151) to reveal reasons hindering the development of organic production in the North-West. The motivation features of small business in the today’s institutional environment depend on typological characteristics of producers: “highly motivated”, “lowly motivated”, and “conditionally motivated”. Thus, despite some respondents’ interest in the transition to organic agriculture, there are factors preventing such a transition, and one of the most important is the need for increased government support, including in marketing. The authors conclude that mainly the risks of not getting the desired economic result influence intentions and plans of such producers, regardless of the location of the farm, which explains the need for special target programs at the regional level to stimulate the business sector, including the study of the dynamics of producers’ motives and incentives